2005
DOI: 10.1002/jcu.20125
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced power Doppler sonography of malignant ovarian tumors using harmonic flash‐echo imaging: preliminary experience

Abstract: To investigate the potential usefulness of contrast-enhanced intermittent harmonic sonography in the diagnosis of ovarian cancer, we evaluated 4 patients with complex adnexal masses suspected of malignancy using intermittent harmonic sonography after injection of a contrast agent. Tumor and/or mural nodule tissue enhancement was detected in all cases of ovarian malignancy. Contrast-enhanced, intermittent harmonic sonography provides a satisfactory visualization of blood flow in the solid portion of the tumor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…After screening titles and abstracts, a further 55 were excluded. After examination of the full text of the remaining 48 candidate studies, a further 34 were excluded, leaving 14 articles considered as being eligible for the systematic review. Three of these were not eligible for meta‐analysis due to missing sensitivity, specificity, accuracy or correlation values; thus, 11 studies were eligible for the meta‐analysis according to our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening titles and abstracts, a further 55 were excluded. After examination of the full text of the remaining 48 candidate studies, a further 34 were excluded, leaving 14 articles considered as being eligible for the systematic review. Three of these were not eligible for meta‐analysis due to missing sensitivity, specificity, accuracy or correlation values; thus, 11 studies were eligible for the meta‐analysis according to our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The I 2 values for sensitivity, specificity and DOR were 38.3%, 31.7% and 48.4%, respectively, indicating moderate heterogeneity for all three. The conclusions from three studies that examined CE‐US but were not included in the quantitative analysis were also assessed (data not shown); all three suggested that CE‐US is useful for discriminating benign from malignant ovarian tumors.…”
Section: Resultsmentioning
confidence: 99%
“…CEUS utilizes harmonic and pulse inversion techniques, with its frequency setting, and the probe can only accept nonlinear echo of microbubbles with specific enhancement, while filtering out the fundamental and intrinsic echo, which can effectively enhance the two-dimensional ultrasound imaging and flow Doppler signal of a parenchymatous organ, clearly showing tissue perfusion [ 16 , 17 ]. Based on the characteristics of CEUS, we can perform a further 2D-CEUS examination of the solid echo lesion, which are difficult to distinguish by 2D gray scale or CDFI examination.…”
Section: Discussionmentioning
confidence: 99%
“…While gray‐scale ultrasound is used routinely, contrast‐enhanced ultrasonography has been slow to reach the reproductive medicine clinic. Contrast‐enhanced power Doppler ultrasound has only rarely been reported in the clinical diagnosis of ovarian tumors, which have the highest mortality rate of any of the gynecologic malignancies, but its ability to confirm a diagnosis remains unconfirmed [Heintz et al, ; Kohzuki et al, ]. While preliminary studies with contrast agents remain inconclusive [Fleischer et al, ; Testa et al, 2007], further research to optimize routine contrast‐enhanced ultrasonography of the ovary may increase the detection of much smaller ovarian tumors than are currently detectable by gray scale and Doppler ultrasound imaging, thereby diagnosing this deadly cancer at a stage when treatment can be initiated to improve survival rates.…”
Section: Discussionmentioning
confidence: 99%